KORELASI KINERJA GURU DENGAN PRESTASI BELAJAR SISWA KELAS V SDN GUGUS 5 KEC. CAKRANEGARA TAHUN AJARAN 2020/2021 - Yuniarti, Titin; Karma, I Nyoman; Jaelani, Abdul Kadir (Jurnal Ilmiah Widya Pustaka Pendidikan, 2023)
This study aims to determine the relationship between teacher performance and learning achievement at SDN Gugus V, Cakranegara District. The research was carried out in 5 SDN cluster V, Cakranegara District in class V for the 2020/2021 academic year. The research method uses Ex Post Facto with a sample of 70 students with proportionate random sampling technique. Data collection techniques used are questionnaires and documentation studies. The results showed that the teacher's performance was in a good category and the correlation between teacher performance and student achievement was weak with a value of r: 0.603 and a value of p: 0.000 <0.05, which means that there is a relationship between teacher performance and student achievement.